SAFETY OF ULTRASONIC DISSECTION VERSUS CONVENTIONAL ELECTROCAUTERY DISSECTION DURING LAPROSCOPIC CHOLECYSTECTOMY IN TERMS OF GALL BLADDER PERFORATION - Khan, Nadim; Ahmad, Munir; Ahmad, Zahoor; Khan, Amjad; Sadiq, Muzafar-uddin (Journal of Postgraduate Medical Institute, 2013)
Objective: To compare the safety of ultrasonic and electrocautery method of dissection in terms of gallbladder perforation. Methodology: This randomized controlled trial included 128 patients, which were divided into two groups,ultrasonic dissection (A) and electrocautery dissection (B). GB perforation (if any) was notedintraoperatively, and all the data was recorded on a structured questionnaire. Data was analyzed using SPSS. Results: The incidence of GB perforation was significantly lower in ultrasonic dissection (10.9%) than electrocautery methods of dissection (29.7%), hence the safety of ultrasonic dissection in terms of gallbladder perforation, was significantly higher than electrocautery dissection (89.1% vs. 70.3% p-value=0.007). Conclusion: ultrasonic dissection is safer modality of dissection in terms of gall bladder perforation andits use should be encouraged as routine method of dissection during LC.